Pemberdayaan Siswa Sekolah Dasar Sebagai Duta Kesehatan Melalui Program Dokter Cilik untuk Meningkatkan Kesadaran Hidup Sehat di Lingkungan SD Negeri 1 Aikmel Utara dan Sekitarnya - Zulfadli Hamdi; Muhammad Mirwan Apriandi; Enki Rizaldo; Sapma Dewi Anggraini; Lilik Suriani; Baiq Risa Apriantari; Maeli Astuti (Alpatih Harapan Semesta, 2025)
The empowerment of elementary school students as health ambassadors is a strategic effort to enhance awareness of healthy living within schools and surrounding communities. This study aims to examine the effectiveness of the